2005
DOI: 10.1111/j.1523-1755.2005.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury and progressive loss of peritubular capillaries in the development of chronic allograft nephropathy

Abstract: CAN was characterized by progressive injury to the renal microvasculature and the development of renal scarring. In particular, injury, angioregression and progressive loss of the PTC network strongly contributed to the development of interstitial fibrosis and graft dysfunction in CAN, and might play a crucial role in the development of CAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 41 publications
5
94
1
Order By: Relevance
“…In chronic rejection, T-cell-dependent and antibody responses target the endothelium, contributing to a sustained increase in endothelial apoptosis [6][7][8][9][10][11][12]55]. In turn, endothelial apoptosis leads to a state of hyperadhesiveness, facilitating the recruitment and emigration of lymphocytes and macrophages [56] but also hMSC [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic rejection, T-cell-dependent and antibody responses target the endothelium, contributing to a sustained increase in endothelial apoptosis [6][7][8][9][10][11][12]55]. In turn, endothelial apoptosis leads to a state of hyperadhesiveness, facilitating the recruitment and emigration of lymphocytes and macrophages [56] but also hMSC [23].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of chronic renal, heart and, more recently, lung rejection, increased endothelial apoptosis was shown to correlate with CTV development [5][6][7][8][9][10]. Also, the sustainability of the endothelial apoptotic response within human renal and heart allografts was found to be tightly associated with CTV [11,12]. In most forms of pathologic vascular remodeling, including CTV, neointima formation is characterized by subendothelial accumulation of a smooth muscle actin (aSMA)-positive cells, extracellular matrix (ECM) components, and mononuclear leukocytes [2].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Endothelial cell (EC) apoptosis is increasingly recognized as an early pathogenic event in fibrosis. A wide array of fibrogenic conditions, such as systemic sclerosis, 4,5 graftversus-host disease 6,7 and chronic rejection of solid allografts, 8,9 has been associated with increased EC apoptosis. Pathophysiological pathways linking endothelial apoptosis to fibrogenesis are still poorly defined.…”
mentioning
confidence: 99%
“…Indeed, clinical biopsy studies have shown an association between loss of tubular structure and function on the one hand and capillary rarefaction on the other. 11,12 Because of their limited replicative capacity, renal ECs are thought to be insufficiently capable to completely repair the injured endothelium of the peritubular capillary plexus after IRI. 13,14 Therefore, current therapeutic strategies to prevent microvascular loss have focused on the prevention of pericyte perturbation to reduce capillary rarefaction.…”
mentioning
confidence: 99%